Konsep Manajemen Pengembangan Musyawarah Guru Mata Pelajaran (MGMP) Dalam Upaya Meningkatkan Kompetensi Profesional Guru - Nur Hidayah (Departement of Mathematics Education, 2023)
Teacher professionalism is a significant aspect in determining success in classroom learning activities. This research is a literature review that aims to understand the development of MGMP management in an effort to improve teacher professionalism. The results of the study show that the MGMP development management has several basic standards in carrying out its projects, including regulating appropriate project plans so that the objectives of the MGMP program can be identified. Separation is deciding on the constructs of the individuals involved with the MGMP so that each one's obligations or commitments are clear to drive the MGMP program. Development is the stage where there are known substantial exercises related to the MGMP programs that have been prepared. Next is supervision, especially the stage where a program requires control and assessment so that the program runs better. The presence of the MGMP has a very big commitment to increasing the capabilities of educators, especially for the purposes of examining instructors, strengthening learning materials, and strengthening instructor abilities.